Effect of neurocentral cartilage destruction on spinal growth in immature rabbits. Issue 2 (February 2019) - Wen, Jie; Wang, Dahui; Fang, Ke; Xiao, Sheng; Ma, Ruixue; Liu, Hong
Objective: This study was performed to observe the effect of neurocentral cartilage (NCC) destruction on spinal growth in immature rabbits. Methods: The NCC of the lumbar vertebrae of 24 4-week-old female rabbits was destroyed through posterolateral and anterior approaches, and three-dimensional computed tomography examinations were performed 3 months after the procedure. Results: Scoliosis was successfully induced in all rabbits of both the anterior and posterolateral approach groups. The scoliosis exceeded 10 degrees in three rabbits, which exhibited coronal scoliosis of the spine, unequal length and thickness of the bilateral pedicles, and rotation of the vertebrae. Scoliosis was not observed in the control group. Conclusions: Destruction of the unilateral NCC in immature rabbits can induce structural scoliosis, similar to the pathological features of human scoliosis. The Cobb angles are similar after NCC destruction by a posterolateral approach and under direct vision via the anterior approach.